Exosomes from cisplatin-induced dormant cancer cells facilitate the formation of premetastatic niche in bone marrow through activating glycolysis of BMSCs - Xu, Jiaqi; Feng, Xiang; Yin, Na; Wang, Lujuan; Xie, Yaohuan; Gao, Yawen; Xiang, Juanjuan (Frontiers in Oncology, 2022)
Introduction Lung cancer is the leading cause of cancer-related deaths worldwide. Chemotherapy kills most cancer cells; however, residual cells enter a dormant state. The dormant cancer cells can be reactivated under specific circumstances. The “premetastatic niche” that is suitable for colonization of cancer cells is formed before the arrival of cancer cells. Tumor-derived exosomes are the main mediators of tumorigenesis. We are aiming to elucidate the roles of exosomes from cisplatin-induced dormant lung cancer cells in the formation of premetastatic niches in bone marrow. Methods We performed differential proteomics in dormant A549 cell- and A549 cell-derived exosomes. Non-targeted metabolomics and RNA sequencing were performed to explore the molecular and metabolic reprogramming of bone marrow stromal cells (BMSCs). The growth and metastasis of A549 cells in vivo were monitored by bioluminescence imaging. Results We found that Insulin-like growth factor 2 (IGF-2) and Insulin-like growth factor binding protein 2 (IGFBP2) were upregulated in dormant A549 cell-derived exosomes. BMSCs that took up exosomes from dormant A549 cells showed enhanced glycolysis and promoted the growth and metastasis of A549 cells possibly through Insulin-like growth factor 1 receptor (IGF-1R)-induced metabolic reprogramming. Inhibition of the production of lactate and IGF-1R signaling can suppress the growth and metastasis of A549 cells from bone marrow. Discussion Overall, we demonstrated that BMSCs formed a premetastatic niche upon taking up exosomes from cisplatin-induced dormant lung cancer cells. BMSCs promoted lung cancer cell growth and metastasis through the reverse Warburg effect.